The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0741-5214(98)70227-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical wall stress in abdominal aortic aneurysm: Influence of diameter and asymmetry

Abstract: Our computer models showed that the stress within the wall of an abdominal aortic aneurysm and possibly the potential for rupture are as dependent on aneurysm shape as they are on maximum diameter. This information may be important in determining severity of individual abdominal aortic aneurysms and in improving understanding of the natural history of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
328
0
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(362 citation statements)
references
References 21 publications
21
328
0
13
Order By: Relevance
“…Also, it can lead to an increased rupture risk and aneurysm dilatation with growing systolic and mean pressure after TAVI and the increase in wall stress. 13,14) Likewise, an aneurysm operation in a patient with severe aortic stenosis presents high-risk. Surgical aneurysm repair had a high-risk because of the very severe aortic stenosis in our case as well.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it can lead to an increased rupture risk and aneurysm dilatation with growing systolic and mean pressure after TAVI and the increase in wall stress. 13,14) Likewise, an aneurysm operation in a patient with severe aortic stenosis presents high-risk. Surgical aneurysm repair had a high-risk because of the very severe aortic stenosis in our case as well.…”
Section: Discussionmentioning
confidence: 99%
“…Gijsen et al (1997) suggested a new experimental technique to determine the wall shear stress in vivo. Vorp et al (1998) used a coupled fluid structure interaction model to combine the influence of mechanical stress and wall shear stress and concluded that the arterial diseases are most probably localized in regions of high mechanical stress and low wall shear stress. However, the mechanical stress within the wall cannot easily be extracted unless further development in imaging techniques and image segmentation algorithms are achieved.…”
Section: Article In Pressmentioning
confidence: 99%
“…Although being studied by many authors (e.g. Womersley, 1955;McDonald, 1974;Caro et al, 1978;Ku et al, 1985;Moore et al, 1994a, b;Reneman et al, 1993;Taylor et al, 1996;Gijsen et al, 1997;Vorp et al, 1998;Wootton and Ku, 1999), the relation between flow fields and cardiovascular diseases is still not fully understood, and is currently receiving more and more attention (Botnar et al, 2000;Berthier et al, 2002;Cheng et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The AAA arises in the infrarenal aorta with a diameter greater than 3 cm and can be up to 9 cm in length [1,2]. Most of the studies on aneurysms have focused on already existing realistic or idealized aneurysms [33][34][35][36][37][38][39][40][41][42][43] with the aim of defining a relevant rupture criterion [4,7,10,19,20,24]. The ratio of the vessel stress to vessel strength is regarded as an alternative tool to conventional diameter criteria, which may be insufficient in small aneurysms.…”
mentioning
confidence: 99%
“…The ratio of the vessel stress to vessel strength is regarded as an alternative tool to conventional diameter criteria, which may be insufficient in small aneurysms. In computational simulations, vessel stress is calculated as a function of the vessel diameter [7,34], wall thickness [36,37], asymmetry [14,18,34,36], tortuosity [21], material property [17,24,29,38], calcification [15,22], intraluminal thrombus (ILT) [5,15,16,33], and blood flow [4, 9, 13, 14, 17, 20, 25, 26, 28-30, 32, 35-41]. Blood vessel strength is measured by ex vivo studies [11,12,23,31,44] or estimated by effective features such as ILT existence, sex, and genetic vulnerability [10].…”
mentioning
confidence: 99%